El obstruccionismo parlamentario (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2012)
Parliamentary obstructionism is a phenomenon that in spite of being seldom used nowadays, as a result of the precise requirements contained in the Regulations of the Parliaments, is a practice still used by the members of the Parliaments.The origin of the obstructionist tactics in Anglo-Saxon parliamentarism is analyzed in this article, as well as the ones referred to the Continent, in so far as the rationalization of parliamentarism has helped to mitigate the development of these practices. We examine the nature, character, classes and obstructionism elements and we put together the most frequently used tactics and also the legal solutions adopted to put them an end, focusing on the methods of curtailing debate, analyzing the Regulations at “Cortes Generales” as well as at “Parlamentos Autonómicos”.Finally, we conclude this work by examining the obstructionism from the legal, political and ethical outlook.